Not all anaemia is from cancer: unmasking carboplatin-induced haemolysis - Mohd Moni, Noor Hidayah; Tan, Ying Li; Ismail, Irnani (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2026)
Introduction: Carboplatin is an alkylating anti-neoplastic agent commonly used in ovarian cancer. Its main toxicity is myelosuppression, while immune-mediated haemolysis is rare. The true incidence of carboplatin-induced haemolytic anaemia is unknown, but drug induced immune-mediated haemolytic anaemia (DIIHA) is estimated to occur in approximately 1 in 1,000,000 patients. Cases may be overlooked because anaemia is common during treatment. Here we report a case of cervical cancer treated with Carboplatin and developed carboplatin-induced haemolytic anaemia. Case summary: A 74-year-old woman with cervical cancer underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy in 2008. Her disease recurred with paravertebral mass in 2021. She had radiotherapy followed by six cycles of carboplatin and paclitaxel. Her disease remained stable until June 2024, when she developed a left supraclavicular lymph node enlargement. FNAC confirmed metastatic squamous cell carcinoma, and she was started on carboplatin and gemcitabine. During cycle 3, she developed severe anaemia (haemoglobin 5.3 g/dL) with no evidence of bleeding. Her blood film suggested haemolysis, with elevated reticulocytes (9.6%) and a positive direct Coombs test (anti-IgG 2+, anti-C3D 3+). Haematology concluded warm autoimmune haemolytic anaemia, likely triggered by carboplatin. She was treated with oral prednisolone (1 mg/ kg) and four cycles of intravenous rituximab. Chemotherapy was later resumed with gemcitabine and cisplatin after completing rituximab without complications. Discussion: Carboplatin-induced immune haemolytic anaemia is exceptionally rare but potentially severe. This case highlights the importance of considering DIHA in patients who develop acute, unexplained anaemia during carboplatin therapy. Prompt recognition, drug withdrawal and immunosuppression is crucial.